Early Nasojejunal Nutrition Versus Early Oral Feeding in Patients After Pancreaticoduodenectomy: A Randomized Controlled Trial - Liu, Xinchun; Chen, Qiuyang; Fu, Yue; Lu, Zipeng; Chen, Jianmin; Guo, Feng; Li, Qiang; Wu, Junli; Gao, Wentao; Jiang, Kuirong; Dai, Cuncai; Miao, Yi; et al. (Frontiers in Oncology, 2021)
Objective: The aim of this study was to test the hypothesis that early oral feeding (EOF) is superior to early nasojejunal nutrition (ENN) after pylorus-preserving pancreaticoduodenectomy (PPPD) in terms of delayed gastric emptying (DGE). Background: DGE is a common complication after PPPD. Although EOF after PPPD is recommended by several international guidelines, there is no randomized trial to support this recommendation. Methods: From September 2016 to December 2017, a total of 120 patients undergoing PPPD were randomized into the ENN, EOF, or saline groups at a 1:1:1 ratio (40 patients in each group). The primary endpoint was the rate of clinically relevant DGE. Secondary endpoints included overall morbidity, postoperative pancreatic fistula, post-pancreatectomy hemorrhage, abdominal infection, length of hospital stay, reoperation rate, and in-hospital mortality. Results: The baseline characteristics and operative parameters were comparable between the groups. The incidence of clinically relevant DGE varied significantly among the three groups (ENN, 17.5%; EOF, 10.0%; saline, 32.5%; p=0.036). The saline group had a higher clinically relevant DGE rate than the EOF group (p=0.014). The saline group also had greater overall morbidities than the ENN and EOF groups (p=0.033 and p=0.006, respectively). There were no significant differences in other surgical complication rates or postoperative hospital stay. No mortality was observed in any of the groups. Conclusions: Nutritional support methods were not related to DGE after PPPD. EOF was feasible and safe after PPPD, and additional ENN should not be routinely administered to patients after PPPD.